198k views
19 votes
Use mathematical induction to prove the statement is true for all positive integers n. 1^2 + 3^2 + 5^2 + ... + (2n-1)^2 = (n(2n-1)(2n+1))/3)

User Jessen
by
6.5k points

1 Answer

13 votes

Answer:

The statement is true is for any
n\in \mathbb{N}.

Explanation:

First, we check the identity for
n = 1:


(2\cdot 1 - 1)^(2) = (2\cdot (2\cdot 1 - 1)\cdot (2\cdot 1 + 1))/(3)


1 = (1\cdot 1\cdot 3)/(3)


1 = 1

The statement is true for
n = 1.

Then, we have to check that identity is true for
n = k+1, under the assumption that
n = k is true:


(1^(2)+2^(2)+3^(2)+...+k^(2)) + [2\cdot (k+1)-1]^(2) = ((k+1)\cdot [2\cdot (k+1)-1]\cdot [2\cdot (k+1)+1])/(3)


(k\cdot (2\cdot k -1)\cdot (2\cdot k +1))/(3) +[2\cdot (k+1)-1]^(2) = ((k+1)\cdot [2\cdot (k+1)-1]\cdot [2\cdot (k+1)+1])/(3)


(k\cdot (2\cdot k -1)\cdot (2\cdot k +1)+3\cdot [2\cdot (k+1)-1]^(2))/(3) = ((k+1)\cdot [2\cdot (k+1)-1]\cdot [2\cdot (k+1)+1])/(3)


k\cdot (2\cdot k -1)\cdot (2\cdot k +1)+3\cdot (2\cdot k +1)^(2) = (k+1)\cdot (2\cdot k +1)\cdot (2\cdot k +3)


(2\cdot k +1)\cdot [k\cdot (2\cdot k -1)+3\cdot (2\cdot k +1)] = (k+1) \cdot (2\cdot k +1)\cdot (2\cdot k +3)


k\cdot (2\cdot k - 1)+3\cdot (2\cdot k +1) = (k + 1)\cdot (2\cdot k +3)


2\cdot k^(2)+5\cdot k +3 = (k+1)\cdot (2\cdot k + 3)


(k+1)\cdot (2\cdot k + 3) = (k+1)\cdot (2\cdot k + 3)

Therefore, the statement is true for any
n\in \mathbb{N}.

User NikitaBaksalyar
by
7.0k points